(untitled) (Journal of Nepalese Business Studies, 2025)
Job satisfaction is the positive perception and feeling of an employee towards the job. The purpose of this study was to determine the level of job satisfaction among non-managerial level commercial banking employees in Pokhara. The non-managerial level commercial banking employees were the respondents of the study. Convenience sampling techniques were used to determine the number of respondents in the study. Convenience sampling techniques were used, and the sample size is 209. To determine the number of respondents, data and information were collected from 209 (102 male and 107 female) respondents through self-structured questionnaires. This study was conducted to fill the gap and to cover a broad area of commercial banking non-managerial level employees’ job satisfaction. Likewise, extrinsic and intrinsic variables were studied to determine the level of job satisfaction. Statistical tools, mean, standard deviation, independent sample t-test, and one-way ANOVA were used to address the research problems. This study revealed that both intrinsic and extrinsic dimensions influenced job satisfaction. However, intrinsic dimensions play a vital role in job satisfaction. In the same manner, female unmarried officer level, and joint venture employees are more job satisfied. This study highlights the importance of focusing on intrinsic dimensions to enhance overall employee job satisfaction and organizational performance.